Crime victim surveys: political relevance and methodological issues - Kyvsgaard, Britta (Improving knowledge on crime, 2009)
Crime victim surveys are of enormous political relevance. Today, such surveys are being used, both at the national and international levels, largely due to the general increasing tendency to use research results in politics.